2011
DOI: 10.1007/s10751-011-0361-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of titanium ion substitution in the barium hexaferrite studied by Mössbauer spectroscopy and X-ray diffraction

Abstract: A series of M-type barium hexaferrite has been synthesized in a glass melt by partially substituting the Fe 2 O 3 with TiO 2 for investigation of their structure. The glass melt has the basic composition (mol%): 40 BaO + 33 B 2 O 3 + (27-x) Fe 2 O 3 + x TiO 2 with x = 0, 3.6, 5.4 and 7.2 mol% TiO 2 . The substituted ferrites were studied by means of X-ray diffraction, Mössbauer spectroscopy and vibration sample magnetometer. X-ray diffraction studies revealed that not all samples have a single ferritic phase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
1
10
0
1
Order By: Relevance
“…The Ti distribution on the different crystallographic sites in BaFe 12−x Ti x O 19 was several times investigated using various techniques but is still under debate. While some data support a substitution of Fe 3+ by Ti 4+ mainly affecting the 12k site, 22 other authors suppose the Ti 4+ ions occupying preferentially the 4f sites at low concentrations. 24,26 However, a combined theoretical and Mossbauer spectroscopic study indicated Ti to be preferentially located on all octahedrally coordinated sites (Fe(1) 2a, Fe(4) 4f, and Fe(5) 12k), while even some substitution should occur at the 2b site (Fe(2), 4e, respectively).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The Ti distribution on the different crystallographic sites in BaFe 12−x Ti x O 19 was several times investigated using various techniques but is still under debate. While some data support a substitution of Fe 3+ by Ti 4+ mainly affecting the 12k site, 22 other authors suppose the Ti 4+ ions occupying preferentially the 4f sites at low concentrations. 24,26 However, a combined theoretical and Mossbauer spectroscopic study indicated Ti to be preferentially located on all octahedrally coordinated sites (Fe(1) 2a, Fe(4) 4f, and Fe(5) 12k), while even some substitution should occur at the 2b site (Fe(2), 4e, respectively).…”
Section: Resultsmentioning
confidence: 89%
“…Although this issue appears not finally settled, 8 cerimetric titrations and Mossbauer studies on Ti-substituted samples give strong indications on the presence of Fe 2+ . 22 PXRD patterns of samples (from bottom to top) 1 to 6 as denoted in Table 1 are presented in Figure 3. Figure 4 shows the development of the unit cell parameters with increasing Fe substitution by Ti.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the Ti 4+ ions prefer the octahedral sites of 12k, 2a and 4f 2 for stability because of their rare gas outer electron shell structure [26, 27]. They can also occupy the 2b site at high doping levels [16]. For the magnetic properties of the ferrite, the anisotropy field H a is related to the sites occupied by Ti 4+ ions.…”
Section: Resultsmentioning
confidence: 99%
“…The parameters of Mössbauer spectroscopy indicate that the Ti 4+ ions occupy the 2a and 12k octahedral crystal structure positions. Upon substitution with a high concentration, the Ti 4+ ions are also located in the 2b pentahedral and 4f vi octahedral positions. However, as found in ref , the Ti 4+ ions occupy mainly the 4f iv tetrahedral and 4f vi and 12k octahedral positions.…”
Section: Introductionmentioning
confidence: 99%